2013
DOI: 10.5751/es-05510-180134
|View full text |Cite
|
Sign up to set email alerts
|

How fit turns into misfit and back: Institutional Transformations of Pastoral Commons in African Floodplains

Abstract: ABSTRACT. We enlarge the notion of institutional fit using theoretical approaches from New Institutionalism, including rational choice and strategic action, political ecology and constructivist approaches. These approaches are combined with ecological approaches (system and evolutionary ecology) focusing on feedback loops and change. We offer results drawn from a comparison of fit and misfit cases of institutional change in pastoral commons in four African floodplain contexts (Zambia, Cameroon, Tanzania (two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
78
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 18 publications
1
78
0
1
Order By: Relevance
“…This is a response to an article in Ecology and Society by Haller et al (2013). In this response, I argue that Haller et al's (2013) description of the pastoralists' management of common-pool grazing resources in the Logone floodplain of Cameroon is incorrect.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…This is a response to an article in Ecology and Society by Haller et al (2013). In this response, I argue that Haller et al's (2013) description of the pastoralists' management of common-pool grazing resources in the Logone floodplain of Cameroon is incorrect.…”
Section: Introductionmentioning
confidence: 90%
“…I argue that Haller et al (2013) have misread the pastoral system in the Logone floodplain, where our studies have shown that there is currently a good fit between local, regional, national, and international institutions and the common-pool grazing resources governed. In addition, I would like to bring into question the claim of Haller et al (2013) that there was an "institutional fit" in the precolonial past.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations